2005
DOI: 10.1007/s00113-005-0942-z
|View full text |Cite
|
Sign up to set email alerts
|

Prothetische Versorgung der proximalen Femurfrakturen

Abstract: The endoprosthetic replacement of the hip joint or its components in fractures of the proximal femur is a standard method. Indications for replacement are strongly dislocated intracapsular femoral neck fractures in elderly patients, fractures with an existing arthritis of the hip joint, and profound osteoporosis. Improved perioperative management and more gentle anesthetic techniques have helped to reduce perioperative mortality from nearly 50% to 11.5% over the last 40 years. As routine treatment options, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
8
0
10
Order By: Relevance
“…6% [4], die Einjahresmortalität bei ca. 27% [2]. Hieraus ist ersichtlich, welche enormen Auswirkungen eine Schenkelhalsfraktur für den älteren Menschen mit sich bringt.…”
Section: Hohe Mortalität Und Morbiditätunclassified
See 1 more Smart Citation
“…6% [4], die Einjahresmortalität bei ca. 27% [2]. Hieraus ist ersichtlich, welche enormen Auswirkungen eine Schenkelhalsfraktur für den älteren Menschen mit sich bringt.…”
Section: Hohe Mortalität Und Morbiditätunclassified
“…Dennoch ist eine optimale Versorgung der Schenkelhalsfraktur eher im Tagesprogramm als zu später Nacht gewährleistet, da weiterhin der wichtigste Prognosefaktor eine gute Reposition (bei Osteosynthesen) und eine fehlerfreie Implantation bei Prothesen ist [2]. Nötige Revisionen aufgrund von Luxationen, Lockerung oder Infektionen sind eine extreme Belastung für die äl-teren Patienten und gehen regelhaft mit einem schlechten Outcome einher.…”
Section: Optimierung Des Präoperativen Managementsunclassified
“…Absence of sclerotic subchondral bone in the acetabular region, evident in degenerated hip and poorer quality of the bone (osteoporosis) in older patients, worsen the conditions for long-term fixation of components in contrast to the situation in patients undergoing THA due to degenerative changes of the hip [3,10,[25][26][27]33,46,47].…”
Section: Clinical Outcomes -Hhsmentioning
confidence: 99%
“…Primary total hip arthroplasty (THA) for displaced intracapsular fractures of the femoral neck, according to most authors, is indicated in patients who are older than 70 years, physically active and cooperative, and in a good general condition [1][2][3][4][5][6][7][8][9]. However, some authors point out that the rate of complications in the early postoperative period and failures of the arthroplasty later due to loosening of individual components is higher when compared to the rate of complications following THA for osteoarthritis [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The proximal femur fracture is one of the most common injuries of the elderly people and still involves a high rate of complications [1], though perioperative mortality has been reduced from 50 to 11.5% within the last 40 years [2]. Due to osteoporosis as seen in most patients of this age the stability of the bone is reduced and small accidents might lead to fractures of the bone [3].…”
Section: Introductionmentioning
confidence: 99%